Effectiveness of Customary Legal Policy in Handling Rabies in Bali (Case Study in Sega Village, Karangasem Regency, Bali - Sudarma Putra, Ida Bagus; Widnyana, I Made Adi; Kusuma Wardhani, Ida Ayu Sri; Kantriani, Ni Ketut (Journal of Neonatal Surgery, 2025)
The spread of the rabies virus in Bali in the last three years is quite worrying, this is shown by the high number of rabies cases in Bali which are indicated to be caused by transmission from pets as vectors, such as dogs. The life of the Balinese people who free dogs as pets is indeed a supporting factor in the rapid spread of the rabies virus, for this reason it is necessary to implement legal policies that are able to control and deal with the danger of rabies in Bali. The existence of the existing law is felt to be not effective enough to reduce the rate of spread of rabies in Bali, so that concrete steps are needed to accelerate the handling of the people in Bali in a product of customary law which is indeed highly respected and obeyed by the people in Bali, most of whom live in unity. indigenous peoples. The purpose of this study was to look at the arrangements for dealing with the danger of rabies in customary law products, one of which was investigated in Sega Traditional Village, Karangasem Regency, Bali and to see how effective the implementation of this customary law was in handling the danger of rabies. The results showed that the management of rabies in Sega Traditional Village as a research location in Bali was formulated in customary law in the form of pararem, which explicitly obliges indigenous peoples to cage and report their pets to traditional village officials. The existence of this customary law in Sega Traditional Village was able to reduce the number of cases of rabies that occurred, so it was considered effective to be implemented in other villages in Bali